Measuring information dependency for construction engineering projects - Liao, Pin-Chao; Thomas, Stephen R.; O’Brien, William J. (Journal of Civil Engineering and Management, 2013)
Information dependency may be the most important key for managing information exchange to reduce project risks. Studies to date have not successfully discovered objective and quantitative surrogate to measure information dependency. This paper suggests an approach to measure information dependency with the productivity relationships among various disciplines for heavy industrial engineering projects. As part of a Construction Industry Institute (CII) study, the authors identified the information exchange pattern of engineering disciplines. Based on the patterns, the authors discovered the information dependency that various engineering disciplines had with their productivity relationships and conducted a survey afterwards for validation. Both results show significant and consistent evidence suggesting that: 1) information of equipment and piping disciplines is statistically dependent rather than the other paired disciplines; and 2) productivity relationship can be a legitimate surrogate to measure information dependency between equipment and piping disciplines. As such, this study enlightens a research trajectory for improvement of engineering productivity.